A study on factors contribute towards neighborhood safety among residents at Seremban, Negeri Sembilan / Muhammad Khairill Hamzan and Nurliyana Izzaty Abdul Nizam - Hamzan, Muhammad Khairill; Abdul Nizam, Nurliyana Izzaty (2022)
The purpose of this study is to determine the factors that contribute towards neighbourhood safety in Seremban, Negeri Sembilan. The research for this study was conducted from October 2021 to June 2022. This study targeted 100 respondents which are Seremban residents. In addition, the target of the study achieved as there are more than 100 respondents contributed to answer the survey. There are independent variables involved in this study which are sufficient lighting, drain system and lastly location. The data collection method used in this study is questionnaire where the questions is distributed through electronic method. The survey was conducted in Google Form while it is been distributed to the respondents through WhatsApp. The advantages of this method are it is inexpensive, can reach the people easily and fast delivery. The results of the survey were analyse through IBM SSPSS Statistic. Based on the findings, all of the independent variables involved has a significant relationship with the dependent variables which is neighbourhood safety.